Felieton jako stylistyczna swoboda wypowiedzi (na przykładzie tekstów Macieja Stuhra) = Felicity as stylistic freedom of expression (on the example of Maciej Stuhr`s texts) - Gaweł, Sara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The following work "Felicity as stylistic freedom of expression (on the example of the texts of Maciej Stuhr)" presents selected stylistic means used by the columnist (M. Stuhr) in pursuit of the title freedom of expression. The considerations are based on M. Stuhr`s texts, which appeared regularly in the magazine "Zwierciadło" in 2009-2013, and were later collected and published as a collection of columns "In a crooked mirror". In her reflections, the author referred to a number of other scholarly studies treating the columnist as a genre and the literary phenomena occurring in it.
Keywords: felieton; swoboda wypowiedzi; sarkazm; subiektywizm; column; free speech; sarcasm; subjectivity